The Ethics of Free Speech in Social Media: A Human Rights Review - Putri Peni Nur Izzati (Yayasan Mentari Madani, 2023)
This article discusses the importance of ethics in the context of freedom of expression, focusing on its relation to human rights. Freedom of expression is one of the fundamental rights recognized in international human rights declarations. However, its implementation is not always without ethical dilemmas. In this paper, we outline the basic concepts of human rights and describe how freedom of expression is an important element in securing and protecting these rights. Next, we explore the various ethical challenges that arise when this right is exercised, including in contexts of controversy and extremism. We also discussed the responsibility of individuals in exercising their freedom of speech, with an emphasis on restrictions imposed by law on humiliation, social division, and incitement to violence. Within this framework, this article considers the ethical limits of freedom of speech that respect other human rights. Finally, we outline the importance of dialogue and mutual respect in striking a balance between ethics and freedom of expression. Through this analysis, this article aims to promote awareness of the importance of considering ethics in the use of free speech in order to protect fundamental human rights